A multi-shot target wheel assembly for high-repetition-rate, laser-driven proton acceleration - J. Peñas; A. Bembibre; D. Cortina-Gil; L. Martín; A. Reija; C. Ruiz; M. Seimetz; A. Alejo; J. Benlliure (High Power Laser Science and Engineering, 2024)
A multi-shot target assembly and automatic alignment procedure for laser–plasma proton acceleration at high repetition rate are introduced. The assembly is based on a multi-target rotating wheel capable of hosting more than 5000 targets, mounted on a 3D motorized stage to allow rapid replenishment and alignment of the target material between laser irradiations. The automatic alignment procedure consists of a detailed mapping of the impact positions at the target surface prior to the irradiation that ensures stable operation of the target, which alongside the purpose-built design of the target wheel, enables operation at rates up to 10 Hz. Stable and continuous laser-driven proton acceleration at 10 Hz is demonstrated, with observed cut-off energy stability about 15%.